(untitled) (Research, Society and Development, 2021)
Objective: To get to know Forensic Nursing in the compulsory notification of domestic violence in urgency and emergency units to make underreported cases visible. Methodology: Cross-sectional study with descriptive statistic’s methods, considering the analyzed and inferential variables, with the Mann-Whitney U and Spearman correlation tests. The results of independence between the proposed variables were through P values ​​(significance). Results: Most participants were female, aged 25 and 35, and worked at the Base Hospital in São José do Rio Preto. Most of them dealt with violent situations and responded with a violence protocol in the units where they worked. According to the General Forensic Nursing Questionnaire, of the participants who had an acceptable score, less than 20% had forensic knowledge at graduation. The vast majority responded that they pay attention to possible incompatibilities between historical data and clinical findings. Of all participants, 50% describe the characteristics of the injuries. Those participants (n=8) who carry out the Nursing Care Systematization register the events precisely as they do in pre-hospital care. Conclusion: There is a wide possibility for nurses to work in the forensic area, but the professionals interviewed do not have sufficient knowledge about ethical and legal aspects of domestic aggression. Thus, if necessary, it instructs the health professional about recognizing the mandatory notification of violence through the forensic principle and the collection of traces.